Microhabitat use of the diamond darter. Issue 4 (6th May 2013) - Welsh, Stuart A.; Smith, Dustin M.; Taylor, Nate D.
Abstract The only known extant population of the diamond darter (Crystallaria cincotta) exists in the lower 37 km of Elk River, WV, USA. Our understanding of diamond darter habitat use was previously limited, because few individuals have been observed during sampling with conventional gears. We quantified microhabitat use of diamond darters based on measurements of water depth, water velocity and per cent substrate composition. Using spotlights at night‐time, we sampled 16 sites within the lower 133 km of Elk River and observed a total of 82 diamond darters at 10 of 11 sampling sites within the lower 37 km. Glides, located immediately upstream of riffles, were the primary habitats sampled for diamond darters, which included relatively shallow depths (<1 m), moderate‐to‐low water velocities (often < 0.5 m·s−1) and a smooth water surface. Microhabitat use (mean ± SE) of diamond darters was estimated for depth (0.47 ± 0.02 m), average velocity (0.27 ± 0.01 m·s−1) and bottom velocity (0.15 ± 0.01 m·s−1). Substrate used (mean ± SE) by diamond darters was predominantly sand intermixed with lesser amounts of gravel and cobble: % sand (52.1 ± 1.6), % small gravel (12.2 ± 0.78), % large gravel (14.2 ± 0.83), % cobble (19.8 ± 0.96) and % boulder (1.6 ± 0.36). Based on our microhabitat use data, conservation and management efforts for this species should consider preserving glide habitats within Elk River. Spotlighting, a successful sampling method for diamond darters, should be considered for study designs of population estimation and long‐term monitoring.